RETRACTED: Choi, H.-S.; Yang, J. Innovative Use of Self-Attention-Based Ensemble Deep Learning for Suicide Risk Detection in Social Media Posts. Appl. Sci. 2024, 14, 893 - Hoan-Suk Choi; Jinhong Yang (Applied Sciences)
The journal retracts the article titled “Innovative Use of Self-Attention-Based Ensemble Deep Learning for Suicide Risk Detection in Social Media Posts” [...]